Implementación de un sistema web para la gestión de la información de la empresa Maseleg aplicando inteligencia de negocio y la metodología de desarrollo ágil kanban. - Abrigo Llumitaxi, Fernanda Gabriela (2023)
Developing a web-based information management system using business intelligence and the agile Kanban methodology will greatly benefit the Maseleg company. The results of the interview and survey indicate that most of the participants recognize the importance of information management and believe that implementing a web system will improve processes and decision-making. This project will have positive technological, social, and environmental impacts. A detailed analysis of the information requirements is carried out before starting the development of the system using appropriate data tools such as Programming Language: PHP, Framework: Bootstrap, and Database: MySQL. Applying Kanban principles will maximize efficiency during system development and implementation. In addition, the implementation of a web system will centralize the relevant information of the company, which will facilitate access and data management in real-time. By applying business intelligence, a deeper analysis of the data can be carried out, identifying patterns and trends, which will lead to a better understanding of the business and processes. This, in turn, can lead to the identification of opportunities for improvement, optimization of resources, and greater competitive advantage in the market. Similarly, the Kanban agile development methodology is a wise choice for this project, since its incremental and collaborative approach will allow rapid adaptation to changing requirements and continuous delivery of value. This will result in greater satisfaction for both end users and the development team.